2020
DOI: 10.1177/0958928719892843
|View full text |Cite
|
Sign up to set email alerts
|

Public childcare provision and employment participation of East and West German mothers with different educational backgrounds

Abstract: By focusing on a period of a major public childcare expansion in Germany, this study investigates whether higher levels of childcare coverage for under-threes have been positively associated with employment among mothers with different educational backgrounds. Both standard economic labour theories and sociological theories presume that the effect of public childcare provision varies with mothers’ educational attainment. The analysis links county-level data on annual childcare ratios with individual-level data… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 32 publications
1
25
1
Order By: Relevance
“…Accordingly, research in Germany has identified particularly strong effects of full-time care on FLP in general (Boll and Lagemann 2019;Büchel and Spieß 2002). Similarly, full-time care was found to increase the likelihood of full-time employment (Zoch 2020) and part-time employment (20-35 hours) in West Germany (Müller and Wrohlich 2020). Even though the relative importance (in terms of effect magnitude) of full-time care compared to general care provision is not without question (e.g., Boll and Lagemann 2019;Müller and Wrohlich 2020), we assume that, in general, full-time places make it easier to reconcile work and family, and offer greater labor market opportunities than general care provision.…”
Section: Theory and Empirical Research On Public Childcare And Female...mentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, research in Germany has identified particularly strong effects of full-time care on FLP in general (Boll and Lagemann 2019;Büchel and Spieß 2002). Similarly, full-time care was found to increase the likelihood of full-time employment (Zoch 2020) and part-time employment (20-35 hours) in West Germany (Müller and Wrohlich 2020). Even though the relative importance (in terms of effect magnitude) of full-time care compared to general care provision is not without question (e.g., Boll and Lagemann 2019;Müller and Wrohlich 2020), we assume that, in general, full-time places make it easier to reconcile work and family, and offer greater labor market opportunities than general care provision.…”
Section: Theory and Empirical Research On Public Childcare And Female...mentioning
confidence: 99%
“…However, the overall effect becomes insignificant when controlling for county-specific time trends, while the effect of full-time care net of county-specific time trends is not reported (Müller and Wrohlich 2020, Table A-5). Zoch (2020), by combining the childcare data with the SOEP and drawing on multinomial models with an entropy matching procedure, reports a positive relationship between the availability of full-time places for toddlers and maternal employment.…”
Section: Theory and Empirical Research On Public Childcare And Female...mentioning
confidence: 99%
See 1 more Smart Citation
“…With the dominant modernised male-breadwinner model in Germany, men rarely reduce their working hours after childbirth (Zoch 2020). Hence, full-time working mothers usually also have full-time working partners, whereas the opposite is not the case.…”
Section: Division Of Paid and Unpaid Workmentioning
confidence: 99%
“…Previous literature on the reforms of the third phase has indicated a positive relationship between public childcare provision and maternal employment (Boll and Lagemann, 2019). Mothers with at least a vocational degree, with a second child, and who had access to full-time childcare profited most (Zoch, 2020).…”
Section: Employment Opportunities and Public Childcarementioning
confidence: 99%